2020
DOI: 10.1128/msphere.00764-19
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Uptake, Mediated by SloABC and MntH, Is Essential for the Fitness of Streptococcus mutans

Abstract: Early epidemiological studies implicated manganese (Mn) as a possible caries-promoting agent, while laboratory studies have indicated that manganese stimulates the expression of virulence-related factors in the dental pathogen Streptococcus mutans. To better understand the importance of manganese homeostasis to S. mutans pathophysiology, we first used RNA sequencing to obtain the global transcriptional profile of S. mutans UA159 grown under Mn-restricted conditions. Among the most highly expressed genes were t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 70 publications
3
81
0
2
Order By: Relevance
“…Mn levels have been found to be related to each of these systems in other gram-positive bacteria (Kehres and Maguire, 2003;Colomer-Winter et al, 2017). Mn depletion does not appear to induce a traditional stress response, although expression of an oxidative stress tolerance protein, Dpr, significantly increased, which is consistent with a recent study on Mn depletion in S. mutans (Kajfasz et al, 2020). Here we highlight Mn-related systems we identified in this study of S. sanguinis for future investigation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Mn levels have been found to be related to each of these systems in other gram-positive bacteria (Kehres and Maguire, 2003;Colomer-Winter et al, 2017). Mn depletion does not appear to induce a traditional stress response, although expression of an oxidative stress tolerance protein, Dpr, significantly increased, which is consistent with a recent study on Mn depletion in S. mutans (Kajfasz et al, 2020). Here we highlight Mn-related systems we identified in this study of S. sanguinis for future investigation.…”
Section: Discussionsupporting
confidence: 86%
“…The connection between Mn and sugar catabolism is not unprecedented, as previous studies have implicated Mn as important for the activity of carbon catabolism enzymes in other bacteria (Kehres and Maguire, 2003). Additionally, recent studies in S. pneumoniae and S. mutans have shown that fluctuations in metal homeostasis influence the regulation of carbohydrate metabolism (Burcham et al, 2020;Kajfasz et al, 2020). One possible explanation for the Mn-dependent, glucose-independent CcpA repression observed in our study is the accumulation of the glycolytic intermediate, fructose-1,6-bisphosphate (FBP) during Mn depletion (Figure 7).…”
Section: Mn Depletion Leads To Glucose-independent Changes In the Regmentioning
confidence: 99%
“…A number of the differentially expressed genes belong to two large polycistronic transcriptional units (smu193c-smu217c) and (smu1750c-1764c) coding, respectively, for hypothetical proteins of unknown function and the CRISPR2-cas system, a defense mechanism believed to provide immunity against phage invasion (32). In S. mutans UA159, the two CRISPR systems are also linked to stress responses, though the reason for this association remains to be determined (33). For visualization purposes, a dot plot graph showing all genes differently expressed in UA∆perR is provided (Fig.…”
Section: Disruption Of Perr Enhances the Tolerance Of S Mutans To Pementioning
confidence: 99%
“…For RNA-Seq analysis, samples were prepared as previously described (33). Sample quality and quantity were assessed on an Agilent 2100 Bioanalyzer at the University of Florida Interdisciplinary Center for Biotechnology research (UF-ICBR).…”
Section: Western Blot Analysis Wholementioning
confidence: 99%
“…Specifically, S. mutans SloR regulates an ABC-type metal ion transport operon comprised of the sloABC genes, by mechanisms that have been previously described (23,9,24,22). A more recent report describes an ancillary metal ion transporter, called MntH, that helps maintain intracellular metal ion homeostasis in S. mutans, and which bears similarity to Nramptype transporters (25). Taken together, the SloABC and MntH transporters as well as their regulators are essential for ensuring S. mutans fitness and survival in both healthy and dysbiotic plaque environments (9,25,26).…”
Section: Introductionmentioning
confidence: 99%